Jawabanmu

2014-04-09T07:08:59+07:00
F(-3)= -3a+b = -15 
f(2) =  2a+b =  0 -
           -5a  = -15
           
               a = -15 = 3
                     -5

-3a+b = -15
-3(3)+b = -15
-9+b = -15
b = -15 + 9
b = -6

f(5)= ax+b
     = 3(5)+(-6)
     = 15+(-6)
     =9

2014-04-09T07:10:30+07:00
F(x) = ax + b
f(-3) = -3a + b = -15
f(2) = 2a + b = 0

eliminasi
-3a + b = -15
2a + b = 0      
     -5a = -15
        a = 3                             , jadi    2a + b = 0
                                                        2(3) + b = 0
                                                                  b = -6
jadi nilai untuk f(5) = 5a + b = 5(3) + (-6) = 15 - 6 = 9..................

kalau ndk salah kayak gitu, $#@$#$ jngan lupa jdikan yg trbaik yooo..............

1 5 1